CONSIDERATION OF THE CASE IN COURT IN MEDIATION ORDER - Sharipov Asror Safar ugli (Journal Park Publishing, 2024)
The concept of mediation, derived from the Latin word "mediare", refers to, means "mediation". Therefore, in international circulation mediation in the sense of "mediation", " intervention for the purpose of reconciliation applied, and in legal adabièts, the concepts of mediation and mediation are the same meaning acquires. The article focuses on the concept of mediation and its tasks pass.
Keywords: mediation, functions of mediation, purpose of mediation, court, law, dispute, decree, negotiation.